71.5k views
1 vote
F(x) = - 2x
g(x) = 8x^2– 5x+7
Find (f .g)(x).

2 Answers

4 votes

Answer: -16x^3+10x^2-14x

Step-by-step explanation: TCB

User Pravind Kumar
by
5.2k points
7 votes

Answer:


\large\boxed{(f\cdot g)(x)=-16x^3+10x^2-14x}

Explanation:


f(x)=-2x\\\\g(x)=8x^2-5x+7\\\\(f\cdot g)(x)=f(x)\cdot g(x)\\\\\text{substitute:}\\\\(f\cdot g)(x)=(-2x)(8x^2-5x+7)\qquad\text{use the distributive property}\\\\(f\cdot g)(x)=(-2x)(8x^2)+(-2x)(-5x)+(-2x)(7)\\\\(f\cdot g)(x)=-16x^3+10x^2-14x

User Asool
by
5.6k points